Tolloid‐Like 1 Negatively Regulates Hepatic Differentiation of Human Induced Pluripotent Stem Cells Through Transforming Growth Factor Beta Signaling. Issue 2 (2nd January 2020) - Kiso, Ayumi; Toba, Yukiko; Tsutsumi, Susumu; Deguchi, Sayaka; Igai, Keisuke; Koshino, Saki; Tanaka, Yasuhito; Takayama, Kazuo; Mizuguchi, Hiroyuki
Abstract : Single nucleotide polymorphisms in Tolloid‐like 1 (TLL1) and the expression of TLL1 are known to be closely related to hepatocarcinogenesis after hepatitis C virus elimination or liver fibrosis in patients with nonalcoholic fatty liver disease. TLL1 is a type of matrix metalloprotease and has two isoforms in humans, with the short isoform showing higher activity. However, the functional role of TLL1 in human liver development is unknown. Here, we attempted to elucidate the function of human TLL1 using hepatocyte‐like cells generated from human pluripotent stem cells. First, we generated TLL1‐knockout human induced pluripotent stem (iPS) cells and found that hepatic differentiation was promoted by TLL1 knockout. Next, we explored TLL1‐secreting cells using a model of liver development and identified that kinase insert domain receptor (FLK1)‐positive cells (mesodermal cells) highly express TLL1. Finally, to elucidate the mechanism by which TLL1 knockout promotes hepatic differentiation, the expression profiles of transforming growth factor beta ( TGFβ ), a main target gene of TLL1, and its related genes were analyzed in hepatic differentiation. Both the amount of active TGFβ and the expression of TGFβ target genes were decreased by TLL1 knockout. It is known that TGFβ negatively regulates hepatic differentiation. Conclusion: TLL1 appears to negatively regulate hepatic differentiation of human iPS cells by up‐regulating TGFβ signaling. Our findings will provide new insight into the function of TLL1 in human liver development. Abstract : The functional role of TLL1 in human liver development is unknown. Here, we attempted to elucidate the function of human TLL1 using hepatocyte‐like cells generated from human pluripotent stem cells. We found that TLL1 negatively regulates hepatic differentiation of human iPS cells by upregulating TGFβ signaling.